PKM Upaya Peningkatan Kompetensi Guru di Masa Pandemik Covid-19 Untuk Menunjang Pembelajaran Berbasis Digital - Abdul Karim; Moh. Irfan Efendi; Misbahul Huda; Moh. Sholehuddin; Moh. Lutfi Anis; Syaiful Huda (GUYUB: Journal of Community Engagement, 2021)
Since March 16, 2020, the Indonesian government has declared the COVID-19 Pandemic as an extraordinary event. The whole world has felt the impact where this pandemic has changed the lives of people around the world, including in Indonesia. Almost all sectors slumped by this incident, including the education sector. In the education sector, the impact is that the change in the learning model that was originally implemented face-to-face has been changed to online learning to suppress the spread of the coronavirus. This Community Service activity was carried out at Madrasah Tsanawiyah Azzainiyah 2 as the target of the activity, located in Karanganyar village, Paiton sub-district, Probolinggo district. The participants of this activity were all subject teachers at Madrasah Tsanawiyah Azzainiyah 2. Based on the results of the analysis of participant responses, it can be concluded that the implementation of community service has gone as expected. It was proven by the participants' responses that this training can increase teacher knowledge in order to meet the demands of the times, namely digital-based learning.